Study of non-radiation cataract risk factors in chronically exposed persons - L.D. Mikryukova (Офтальмохирургия)
Relevance. Epidemiological data have revealed a significant association between exposure to ionizing radiation, loss of lens optical function, and cataract formation. Cataract is a multifactorial disease that is traditionally associated with age, exposure to ultraviolet radiation, diabetes, smoking, alcohol abuse, obesity, steroid hormones, hypertension, etc. The chronic nature of the effects of radiation on the body, including both cell damage and regenerative processes, complicates the issue of assessment of the nature and magnitude of the dose-dependence of effects. Purpose. To investigate the potential risk factors of cataract development in different morphological layers, depending on social conditions and several diseases (non-radiation factors) in the population affected by two radiation accidents (dumping of radioactive waste into the Techa River and the East Ural Radioactive Trace) in the Southern Urals. Material and methods. The data from an in-depth examination of patients by an ophthalmologist in the Clinical Department of the URCRM were analyzed. The study involved 1377 patients. The «case» and «control» groups, comparable in sex and age, were selected from the general population. The impact of each factor was assessed on the basis of the Odds Ratio (OR) indicator. Risk factors associated with the development of cataracts in different layers of the lens included arterial hypertension, body mass index, age at the onset of exposure, level of education, alcohol consumption, smoking, ethnicity. Results. An increased risk of developing cataracts in the lens nucleus (1stsample: OR=0.54 (1st sample: 95% CI: 0.34–0.86; 2nd sample: OR=0.51 (95% CI: 0.32–0.82) (p<0.05)) and the intensity of its color (1st sample: OR=0.48 (95% CI: 0.29–0.80); 2nd sample: OR=0.56 (95% CI: 0.34–0.94) (p<0.05)) was established in persons who were at the age over 6 at the onset of exposure. Conclusion. The analysis did not reveal a statistically significant relationship of changes in the cortical layers, the nucleus and the posterior capsule of the lens with other studied risk factors in persons exposed to chronic radiation at a low to medium dose range. There was an increased risk of cataract development in the lens nucleus and the intensity of its color in persons who began to be exposed at the age of over 6 years.